Meningkatkan Aktivitas Dan Hasil Belajar Matematika Menggunakan Model PBL, TGT Dan Improve Di SDN Telaga Biru 6 Banjarmasin - Sheila Adella Puteri; Ahmad Muhyani Rizalie (Lembaga Pengembangan Kinerja Dosen, 2023)
The problems that occur in this study are low activity and learning outcomes in Mathematics content, due to the use of limited learning media, learning is less interesting and less fun because learning models and methods are less varied, students are still hesitant in expressing opinions about the material. Efforts are made by implementing learning with a combination of PBL, TGT and Improve models. This study aims to increase the activity and student learning outcomes. This research was centered on fourth grade students at SDN Telaga Biru 6 Banjarmasin, totaling 25 students. The research method used is a qualitative approach with the type of Classroom Action Research (CAR). The data used are qualitative data obtained through observing the activities of teachers and students, while quantitative data is through student learning outcomes from individual written test results. The results showed that the combination of the PBL, TGT and Improve models at the fourth meeting showed that the teacher's activity obtained a score of 92 in the very good category. Student activities get a score of 91 in the very good category. Cognitive, affective and psychomotor completeness learning outcomes reached 88%. Based on the results showed that the combination of Problem Based Learning, Teams Games Tournament and Improve models could increase the activity of teachers, students, and student learning outcomes in Mathematics content.